MAC-PHY Cross-layer design for Secure Wireless Avionics Intra-Communications - Sámano-Robles, Ramiro (2019)
This paper presents a framework for medium access control (MAC) and physical (PRY) cross-layer security design of wireless avionics intra-communications (WAICs). The paper explores the different options based on the latest results of MAC-PRY cross-layer design and the available standard technologies for WAICs. Particular emphasis is given to solutions based on multiple-input multiple-output (MIMO) systems and recent developments towards a wireless technology with ultra-low latency and high reliability in the context of 5G and machine-type traffic support. One major objective is to improve WAICs technology and thus match the real-time, reliability and safety critical performance of the internal aeronautics bus technologies (e.g., ARINC 664). The main identified vulnerabilities and potential solutions are explored, as well as their impact on system design complexity and feasibility for wireless networks on-board aircraft. The solutions are presented in the context of the European project SCOTT (secure connected trustable things) using the recently released reference architecture for trusted IoT systems. Other aspects of SCOTT such as trust, privacy, security classes, and safety are also discussed here for the aeronautics domain.